Knowledge and Perception about Risk Factors and Symptoms of Cervical Cancer in Female Teachers of Government and Private Schools of Chandigarh - Aprajita Singla; N K Goel; Suman Mor; Meenu Kalia (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Cervical cancer ranks as the 2nd most frequent cancer among women in India after Breast Cancer. School Teachers constitute important stakeholder position in the society. The knowledge about cancer cervix is beneficial for them and also to the children they teach. Objective:To assess and compare the knowledge about Cervical Cancer, its risk factors, symptoms and signs prevailing in Female School Teachers of Government & Private Schools in the area of Chandigarh. Method: A Cross-sectional study using multistage random sampling was conducted among Female School Teachers. City was divided in to 4 quadrants, 1 private and 1 Government school was randomly selected from each quadrant. From each quadrant 50 participants were taken in the study. Interview of 202 teachers were conducted through predesigned and pretested questionnaire during February to April 2018. Results: Unawareness about risk factors for cervical cancer was found in 79% of respondents. On asking about risk factors for Cervical Cancer, 8% of participants mentioned that infertility, heredity, use of sanitary pads and depression leads to cervical cancer which shows myths prevailing in community. Awareness about signs and symptoms of Cervical Cancer was found only in 37% respondents. Only 23.8% of Government School Teachers and 37.6% of Private School Teachers were aware about association of HPVwith Cervical Cancer. Conclusion: Low Levels of Awareness about Cervical Cancer was found in the study even in highly educated group of School Teachers belonging to Chandigarh.